Job Training under the New Federalism. JTPA in the Industrial Heartland. Report to the Subcommittee on Employment, Committee on Education and Labor, U.S. House of Representatives - Orfield, Gary.; Slessarev, Helene; Chicago Univ., IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This book-length report, prepared for the Subcommittee on Employment Opportunities of the House Committee on Education and Labor, describes the first comprehensive state-wide assessment of training programs--specifically the Job Training Partnership Act (JTPA)--in Illinois. The introduction assesses the JTPA in Illinois, a State with high unemployment. Chapter 2 reviews research on causes of unemployment and how these relate to training and employment programs. Chapter 3 examines the evolution of Federal job training policy since the early 1970s and analyzes the goals that were the basis of JTPA. Chapter 4 describes the nature of shifts in funding for employment and training programs from the enactment of the Comrepehsnive Employment and Training Act (CETA) in 1975 to the proposed Federal budget for fiscal year 1986. Chapter 5 deals with specific problems of unemployment and reduced job training in Illinois. Chapter 6 discusses the changes occurring between CETA and JTPA. Chapter 7 discusses the role of the States in shaping the JTPA programs. Chapter 8 concerns the absence of data on program impact. Chapter 9 deals with nonenforcement of civil rights. Chapter 10 presents views of JTPA field program operators. Chapters 11 and 12 deal with training and program access. Chapter 13 considers the absence of supportive services. Chapters 14 and 15 consider services to youth and the dislocated worker. In Chapter 16, findings and recommendations are summarized. (CG)
Availability: G. Orfield, 5828 S. University, Chicago, IL 60637 ($5.90 including postage).
Sponsoring Agency: Joyce Foundation, Chicago, IL.
Policymakers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Dislocated Workers; Employment Patterns; Employment Programs; Federal Programs; Federal State Relationship; Job Training; On the Job Training; Program Effectiveness; Public Policy; Unemployment; Youth Programs; Illinois -- Job Training Partnership Act 1982; Comprehensive Employment and Training Act; Reports, Research